Ethics and methods for collecting sensitive data: Examining sexual and reproductive health needs of and services for Rohingya refugees at Cox’s Bazar, Bangladesh - Aktar, Bachera; Ahmed, Rushdia; Hassan, Raafat; Farnaz, Nadia; Ray, Pushpita; Awal, Abdul; Bin Shafique, Sharid; Hasan, Md Tanvir; Quayyum, Zahidul; Rashid, Sabina Faiz (The International Journal of Information, Diversity, & Inclusion, 2022)
This article was published in The International Journal of Information, Diversity and Inclusion [ Copyright (c) 2020 Bachera Aktar , Rushdia Ahmed, Raafat Hassan , Nadia Farnaz, Pushpita Ray , Abdul Awal , Sharid Bin Shafique , Md Tanvir Hasan, Zahidul Quayyum, Mohira Babaeva Jafarovna, Loulou Hassan Kobeissi, Khalid El Tahir, Balwinder Singh Chawla, Sabina Faiz Rashid] and the definite version is available at: https://doi.org/10.33137/ijidi.v4i2.33150 The Journal's website is at: https://jps.library.utoronto.ca/index.php/ijidi/article/view/33150